Models of Attention in Computing and Communication: From Principles to Applications - Horvitz, Eric; Kadie, Carl; Paek, Tim; Hovel, David (Communications of the ACM 46, 2003)
Over the last five years, our team at Microsoft Research has explored, within the Attentional User Interface (AUI) project, opportunities for enhancing computing and communications systems by treating human attention as a central construct and organizing principle. We introduced to the research community a broad array of AUI challenges and opportunities, including (1) the treatment of attention as a rare commodity and critical currency in sensing and reasoning about the information awareness versus disruption of users, (2) the use of attentional cues as an important source of rich signals about goals, intentions, and topics of interest, and (3) the triaging of computation, bandwidth, and rendering resources in guiding precomputation and prefetching with forecasts of future attention. We shall first describe several principles and methodologies centering on integrating models of attention into human-computer interaction. Then, we shall review representative efforts that illustrate how we can harness these principles in attention-sensitive messaging and mixed-initiative interaction applications.